2011
DOI: 10.1140/epjb/e2011-10977-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated fracture of porous media

Abstract: The lifetime of a porous media, submitted to a constant subcritical stress, is studied by means of a numerical model. This model is based on a spring network where the porosity is represented by missing springs. The dynamics is produced adding thermal fluctuations in spring forces. The lifetime predicted by the models are compared to experimental data of delayed fracture of porous media submitted to three-point flexion fracture experiments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In two dimensions, a good approximation of Eq. (3) for random damage is E ≃ E 0 (1 − 2Φ) [38,39]. Thus, we also expect a simple relationship between the temporal evolution of the modulus and the damage as measured by the fraction of broken bonds.…”
Section: Modelmentioning
confidence: 79%
See 1 more Smart Citation
“…In two dimensions, a good approximation of Eq. (3) for random damage is E ≃ E 0 (1 − 2Φ) [38,39]. Thus, we also expect a simple relationship between the temporal evolution of the modulus and the damage as measured by the fraction of broken bonds.…”
Section: Modelmentioning
confidence: 79%
“…However, it was also found that the rate of broken fuses is non monotonous in time: first it decreases mostly as 1/t (thus resulting in a logarithmic decay of the damage) and then it increases until macroscopic rupture occurs [35]. In comparison, the full dynamics of the 2D RFN with disorder and thermal noise is little explored [37,38]. A clear connection between the actual dynamical response of the 2D RFN under constant applied stress and the damage dynamics as a function of disorder, temperature and external loading is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Among the earliest works, Schallamach [1][2][3] introduced one-dimensional models for rubber friction, where friction is assumed to arise from shearing and consequent thermally activated breaking and rebinding of distinct bonds between rubbing members. Since then, rupture models with various degrees of sophistication describe the mechanical response of the rubbing surfaces under deformation forces, for instance, stick-slip dynamics [13,28,29], transition from static to kinetic friction [5], creeping dynamics [30,31], creep and fast dynamics in peeling of polymeric materials [32], the role of temperature in the fracture of soft materials and biological adhesion [33,34], critical behavior characterizing fracture regimes [35][36][37][38], thermally activated rupture [32,[39][40][41]. These models are generic; for instance, further developments of the earthquake model [9] describe different aspects of friction [5,6,42,43], including tuning the friction properties of a hierarchical surface [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Radi et al (2002) considered the steady state crack growth in elastic-plastic porous media. In addition, studies of the thermally activated fracture in porous media were reported by Guarino and Ciliberto (2011).…”
Section: Introductionmentioning
confidence: 99%